216 Effects of Total Equine Grain Containing Ascophyllum Nodosum Seaweed Extract and Chelated Minerals on in-Vitro DMd & Ndfd, Body Composition, and Post-Exercise Recovery in Mature Quarter Horse Mares. (21st September 2022) - Lai, Kai Yun; Porter, Dylan; Boyd, Jamie A
Abstract: Supplements such as seaweed extracts and chelated minerals have been shown to positively affect animal health. However, these supplementation is not well-researched in equines. The purpose of this study was to assess the effects of an extruded grain (Total Equine) containing Ascophyllum nodosum seaweed extract with and without a chelated sulfur supplement (Total Equine-15 Natural) on in vitro DMd and NDFd, body composition, and post-exercise recovery. Six Quarter Horse mares were fed three different diets: Control (Ctrl), Total Equine (TM), Total Equine plus Equine-15 Natural (TM15) in a Latin square design study with a six-week washout period between each three-week experimental period. Grain was offered at 0.004% BW. A submaximal test (4 min at 4.3 mph, 14 min at 9.5 mph, 6 min at 13.5 mph) was conducted on days 0 and 21. Resting and post-exercise blood lactate, respiratory rate, heart rate, and rectal temperature were measured at the start and end of each experimental period. Fecal samples were collected during the last week of each experimental period and analyzed through Daisy ANKOM. Body weight and body composition were evaluated pre- and post-study. Analysis showed no effect (P=0.12) on Bermuda DMd and NDFd among treatments. However, the DMd and NDFd of alfalfa with TE15 were decreased significantly at 24 hr (P=0.0001 and 0.0003, respectively). The other only significant change observed was body composition. Horses on TE15 had greater loss of fat mass (p=0.005), followed closely by the TE. In conclusion, TE did not show any adverse effects on DMd, NDFd, body composition, and post-exercise recovery; TE15 did not change most nutritional and physiological parameters besides decreasing in vitro DMd, NDFd, and body fat mass. The simple effect of the chelated sulfur and Ascophyllum nodosum in equine should be further investigated.